The Influence of Donor Milk Supplementation on Duration of Parenteral Nutrition in Preterm Infants. (May 2020) - Chinea Jiménez, Bibiana; Cabrera Lafuente, Marta; Couce, María L.; Madero, Rosario; Vento, Maximo; Villarino Marín, Antonio; Saenz de Pipaon, Miguel
Background: Data are limited on the association between the use of donor human milk and improvements in feeding tolerance. Objective: To determine the influence of the duration of parenteral nutrition on the growth and morbidity of the breastfed newborn when using donated human milk in the absence of mother's own milk. Methods: We conducted a retrospective study before and after the intervention that compared two groups of newborns ( N = 284; each group n = 142). We used a convenience sample of all newborns ≤32 weeks gestation consecutively admitted in a single unit before (Group 1 between December 2012 and May 2014) or after (Group 2 between October 2014 and December 2016) the availability of donor human milk. In Group 2, donor human milk was administered at least 3 to 4 weeks or until the baby weighed 1, 500 g. Weight was recorded daily and length and head circumference weekly. Parenteral nutrition was continued until enteral feeding volume reached 120 ml/kg/day. Additional variables measured were the number of days with a central venous catheter, age that the enteral feeding volume reached 150 ml/kg/day, and duration of stay. Results: The duration of parenteral feeding was the same before and after: 12 (8.23) and 11 (7.19) days ( p = .822). The z scores for weight and height of newborns was lower in Group 2 = −1.8 (1.0) and −2.3 (1.1) and Group 1 = −1.2 (1.1) ( p < .001) and −1.8 (1.4) ( p = .005). Conclusion: We did not find an association between the administration of donor human milk as a supplement to mother's own milk and reduced number of days of parenteral nutrition. Back translation by Laurence Grummer-Strawn